Fazlur Rahman's Double Movement and It's Contribution to the Development of Religious Moderation - Yusuf, Muhammad; Nahdhiyah, Nahdhiyah; Sadat, Anwar (Universitas Ahmad Dahlan, 2021)
The essential consideration is whether hermeneutics as an alternative approach can provide a dialogue between the texts and reality. This is library research, in which the data sources obtained through various written works, both in the form of books and journals. The study is descriptive qualitative that provides a clear picture and systematic about the methodology of Islamic legal thought Fazlur Rahman understandings.Â To synchronize his background with interpretations, then used a normative theological approach, namely an approach that emphasizes form religious symbols originating from the Quran and sunnah text. The double movement hermeneutic theory is his effort in dialoguing between text and context. He appreciates history and adapts developments in every space and time. He tried to do a two-way movement. First, moving from the context of reality to the historical context of texts. Second, moving from the context of historical facts to the context of contemporary reality. Errors in interpreting text often occur due to the separation between the text from its context. In these circumstances, the double movement theory finds its relevance in making the Quran capable of dialogue with every dynamic that occurs. In this way, the text is always alive and as if it was revealed at this time. It contributes to the development of a paradigm of religious moderation. The double movement has strong historical roots in the science of the Quran, including asbab al-nuzul, makkiyah-madaniyah, and nasikh-mansukh.